Strategi Pengelompokan Kandang Anjing Pada Pusat Konservasi Anjing Liar di Padang Galak, Denpasar: bahasa indonesia - Komang Junida Aryadi; Ni Putu Ratih Pradnyaswari Anasta Putri; I Wayan Runa (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
Dogs and humans benefit from each other, but the Denpasar City Agriculture Service (2019) states that only 30% of the total dog population in Denpasar are owned/cared for and the rest are wild dogs. The author wants to raise this issue in order to improve the quality of life for stray dogs. The Wild Dog Conservation Center facility in Padang Galak Denpasar aims to address the problem of dogs that are not owned or live on the streets. However, proper planning and design is needed to provide adequate facilities and be able to accommodate the community so that they can be treated according to their classification.